THE RELATIONSHIP BETWEEN PRACTICING NURSES’ PERCEPTIONS OF THE WARD SUPERVISOR’S LEADERSHIP STYLE AND THEIR PERFORMANCE IN COMPLETING NURSING CARE DOCUMENTATION - Desi Afriyanti; Tressia Febrianti; Masdiana; Dina Nurdiana (JTH: Journal of Technology and Health, 2026)
Nursing care documentation serves as a key indicator of service quality and patient safety, with nurse performance in completing documentation influenced by factors such as the head nurse's leadership style. At Military Hospital, characterized by a highly disciplined military organizational culture, identifying an appropriate leadership approach is essential to optimizing staff performance. This study aimed to analyze the relationship between staff nurses' perceptions of head nurse leadership style and their performance in completing nursing care documentation. A quantitative correlational design with a cross-sectional approach was employed. The population comprised 79 staff nurses across inpatient wards, with 66 respondents selected via stratified proportional random sampling. Data were collected using structured questionnaires with established validity and reliability (Cronbach's alpha > 0.95), and analyzed through univariate and bivariate methods using Spearman's rho. Results showed that most staff nurses (77.3%; n = 51) perceived their head nurse as exhibiting a democratic leadership style, while 22.7% (n = 15) perceived an autocratic style. Overall staff nurse performance fell into the very good category (mean score 55.68/60). Spearman's rho revealed a significant positive relationship between perceived leadership style and staff nurse performance (p < 0.001; r = 0.420). These findings confirm a significant relationship between staff nurses' perceptions of leadership style and their documentation performance, with democratic leadership associated with better outcomes than autocratic leadership—even within a highly disciplined, hierarchical hospital culture.